Flexing Practices among Public University Students in Medan on Instagram: A Dramaturgical Perspective on Self-Representation in Digital Spaces - Muhammad Rizky Muharram; Fakhrur Rozi (Ali Institute of Research and Publication, 2026)
This study examines the practice of flexing among public university students in Medan on Instagram as part of self-presentation in digital spaces. The study uses a dramaturgical perspective to understand how flexing is displayed as a form of sharing activities, experiences, and moments that reflect lifestyle and digital identity. This research adopts a qualitative approach with a phenomenological method to explore the subjective experiences of informants. Data were collected through in-depth interviews, digital observation, and content documentation from students selected through purposive sampling. Data were analyzed using a qualitative analysis model through data reduction, data display, and conclusion drawing. The findings show that flexing practices are not solely interpreted as showing off wealth or luxury, but are more commonly expressed through sharing daily activities, experiences, and selected moments on Instagram. These practices are closely related to efforts to build self-image and gain social recognition through audience responses such as likes and comments. Flexing thus becomes part of students’ self-presentation in constructing identity and negotiating social position in digital spaces.